Pendekatan Penelitian Komparatif dalam Ilmu Tafsir: Analisis Perspektif Abdul Mustaqim - Iqbal Fatoni; Thobroni, Ahmad Yusam (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Comparative research in the field of Quranic exegesis has a significant impact on the development of Islamic thought and a deeper understanding of the messages of the Quran. This approach is championed by Abdul Mustaqim, a scholar dedicated to advancing Islamic studies in the domain of tafsir (exegesis). This article employs a descriptive-analytical method to explore the concept of comparative research as proposed by Abdul Mustaqim, particularly in addressing critiques that such studies merely juxtapose two or more opinions without engaging in critical and dialectical analysis. Through his monumental work, Epistemology of Contemporary Tafsir, Abdul Mustaqim introduces a comparative methodology aimed at enhancing methodological insights and frameworks in Quranic exegesis, thereby contributing to its academic application. The findings reveal that Abdul Mustaqim's comparative approach fosters more critical, incisive, and epistemologically rich interpretations. However, this approach faces challenges in synthesizing creative outcomes from its analyses. Therefore, further examination of the essence, objectives, and ideal methods of comparative research is necessary to maximize its relevance in tafsir studies.